Altered cytokine levels in pediatric ITP. (September 2015) - Jernås, Margareta; Hou, Yu; Strömberg Célind, Frida; Shao, Linlin; Wang, Qian; Ju, Xiuli; Mellgren, Karin; Wadenvik, Hans; Hou, Ming; Olsson, Bob
Abstract Immune thrombocytopenia (ITP) is an autoimmune disease where platelets are destroyed prematurely. In the majority of children, the disease resolves, but in some, it becomes chronic. Cytokines are important mediators of the immune response and are known to be dysregulated in autoimmune diseases. Therefore, our aim was to investigate differences in plasma levels of cytokines between children with ITP and healthy controls. We had two cohorts of children: one Swedish with 18 children with ITP and seven healthy children and a second Chinese one with 58 children with ITP and 30 healthy children. Plasma levels of chemokine (C-X3-C motif) ligand 1 (CX3CL1), transforming growth factor β1 (TGF-β1), and interleukin 22 (IL-22) were analyzed in both cohorts using enzyme-linked immunosorbent assays (ELISAs). We found lower plasma levels of TGF-β1 and elevated levels of CX3CL1 and IL-22 in children with ITP compared with controls in both the Swedish and the Chinese cohort. In conclusion, all three cytokines differ between pediatric ITP and healthy controls and may, therefore, be potential biomarkers for the disease.